(untitled) (Research, Society and Development, 2024)
The Covid-19 pandemic triggered several changes in the socioeconomic, political and educational fields. Nursing graduates, in turn, felt these impacts in the process of their professional training. Objective: to describe and analyze how students experienced their training process during remote and hybrid teaching in the pandemic context. Method: this is a qualitative, descriptive study, carried out with undergraduate nursing students at a federal university, who experienced emergency teaching during the Covid-19 pandemic. The data collection instrument was a form created on the Google Forms platform, with open and closed questions. Content analysis of the results was carried out. Results: 80 undergraduate nursing students participated in the research. Positive and negative points of the emergency teaching adopted during the Covid-19 pandemic were highlighted. However, remote and hybrid teaching was understood as a necessary teaching strategy for the occasion. Final considerations: emergency teaching adopted during the Covid-19 pandemic, although necessary, demonstrated many limitations in the teaching-learning process, which requires reflection on the different training modalities in higher education.